Azidothymidine induces severe hematological toxicity and hepatic injury in Charles Foster rats - Pandey, Rajat; Singh, Ramakant (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The present study aimed at evaluating the effects of azidothymidine (AZT) on hematologic and biochemical parameters in Charles Foster rats. Methods: Twelve adult healthy Charles Foster rats comprising of six male and six females were selected for study. Test rodents were divided into four groups containing three rodents each. Three males and three females served as control and remaining received AZT drug. Rodents were acclimatized for 10 days and drug was administered for 28 days. After the completion of drug administration, blood samples were collected and analyzed for hematologic parameters, i.e., Hemoglobin (Hb), Packed cell volume (PCV), red blood cell (RBC), Mean corpuscular hemoglobin concentration (MCHC), total leukocyte count (TLC), Mean corpuscular volume (MCV), Platelet count (Plt) using a Fully Automatic Fully Digital Hematology Cell Counter. In addition, biochemical parameters, were measured to assess the effects of AZT on rodent physiology. In-vivo histopathological studies were also performed on vital organs of rodents to understand the effects of drug at tissue level. Results: When compared with the control group, the data indicated a outstanding decrease in Hb, PCV, RBC, TLC and platelets in all test groups, whereas MCHC did not show any major reduction but MCV data suggested a slight increase. Among biochemical parameters, aspartate aminotransferase (AST), alanine aminotransferase (ALT) and alkaline phosphatase (ALP). were found to be remarkably elevated along with elevated bilirubin and reduced albumin, pointing towards a possible liver damage which was later corroborated by liver histopathological study. Conclusions: Above results indicate azidothymidine to be a myelosuppresive and hepatotoxic drug and its usage as an anti-retro viral during highly active anti-retro viral therapy (HAART) regime should be strictly monitored.